Bestm-term trigonometric approximations of classes of (Ψ, β)-differentiable functions of one variable - Fedorenko, A. S. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We obtain an estimate exact in order for the best trigonometric approximation of classes \(L_β ,p^ψ \) of functions of one variable in the spaceL q in the case where 1